Price and Service Competition in a Dual-Channel Supply Chain with Product Customization - Jian Wang; Huijuan Jiang (Complexity)
This paper considers a dual-channel supply chain with product customization. One manufacturer and one retailer are involved. The online direct sales channel sells standard and customized products, and the offline retail channel sells standard products. The prices and service levels of products sold via different channels are differentiated, and the customization level which influences the customization cost and choices of customers is decided by the manufacturer. Three game models are proposed: the manufacturer Stackelberg (MS) model, the retailer Stackelberg (RS) model, and the Nash game model. The price and service decisions of the players are derived. Meanwhile, a service-cost-sharing contract is designed for the MS model. The impacts of price and service competition, service cost, and customers sensitivity to the customization level on the optimal decisions are investigated. Through the numerical analysis, we find that, among the three models, the manufacturer Stackelberg model is the most beneficial game structure for the overall supply chain but has the largest revenue gap between the two members. Second, under price competition and service competition, the manufacturer should differentiate the prices and services for direct sales standard products and customized products according to his market status. Third, the manufacturer should increase customization expenditures to construct his customization production line and provide more diversified products when consumers are more sensitive to product customization.